Platelet-Rich Fibrin Facilitates Rabbit Meniscal Repair by Promoting Meniscocytes Proliferation, Migration, and Extracellular Matrix Synthesis - Wong, Chin-Chean (Int J Mol Sci, 2017)
Although platelet-rich fibrin (PRF) has been used in clinical practice for some time, to date, few studies reveal its role as a bioactive scaffold in facilitating meniscal repair. Here, the positive anabolic effects of PRF on meniscocytes harvested from the primary culture of a rabbit meniscus were revealed. The rabbit meniscocytes were cultured with different concentrations of PRF-conditioned medium, and were evaluated for their ability to stimulate cell migration, proliferation, and extracellular matrix formation. In vivo, meniscal defects were created via an established rabbit animal model and were evaluated by a histology-based four-stage scoring system to validate the treatment outcome three months postoperatively. The in vitro results showed that PRF could induce cellular migration and promote proliferation and meniscocyte extracellular matrix (ECM) synthesis of cultured meniscocytes. In addition, PRF increased the formation and deposition of cartilaginous matrix produced by cultured meniscocytes. Morphological and histological evaluations demonstrated that PRF could facilitate rabbit meniscal repair. The data highlight the potential utility of using PRF in augmenting the healing of meniscal injuries. These advantages would benefit clinical translation, and are a potential new treatment strategy for meniscal repair.